Holistic management of skin neglected tropical diseases through church networks in the Songololo Territory, the Democratic Republic of Congo: a retrospective evaluation - Delphin Mavinga Phanzu; Saidi Kashindi; César-Augustin Muaka Khoso; Frédéric Kitsasa Kamba; Pierre Soki-Kangi Mbombolo; George Gitau; Stefanie Weiland; Melissa Edmiston (Christian Journal for Global Health)
Background: Neglected tropical diseases (NTDs) are a diverse group of conditions caused by a variety of pathogens mainly prevalent among impoverished communities in tropical areas. In addition to disability and morbidity, they cause stigma and reduced quality of life. The Democratic Republic of Congo (DRC) is endemic for several NTDs, including leprosy, Buruli ulcer, and yaws. Given 98.5% of the population in DRC is estimated to be Christian, and churches are often seen as trusted institutions, a pilot project was implemented to Build Church Networks Capacity to End NTDs (BCNCE). The purpose of this study is to assess the results of the project after implementation. Methods: A retrospective mixed-methods evaluation was conducted in 12 health areas in the Kongo Central Province. Quantitative data were reviewed from project reports, including data on suspect and referred cases and services provided. Qualitative data were gathered through 49 in-depth interviews and 16 focus group discussions with key stakeholders, including pastors, lay leaders, health workers, and persons affected. Qualitative data were analyzed to understand perspectives regarding the involvement of faith leaders through church networks in the holistic management of skin NTDs. Results: The project involved 160 churches: 480 religious and lay leaders and 26 health workers participated in training on NTDs. A total of 54,448 people were exposed to awareness sessions, and 441 suspected cases of skin NTDs were referred to the health centers. Thirty-three NTD cases were confirmed and treated. Eighty-one patients benefited from spiritual and emotional support. Results showed faith leaders can support case identification, referral, and psychological and spiritual care in this context. Conclusion: This study assessed the results of the BCNCE intervention and the implications of faith leader engagement in the control of skin NTDs. Results suggest that a comprehensive strategy for controlling NTDs could be enhanced by utilizing church networks, offering a holistic approach to the detection and management of skin NTDs. This strategy covers not only the medical components of the disease, but also social and spiritual dimensions. In appropriate contexts this model could provide a sustainable approach to case identification, stigma reduction, and psychospiritual support.